CARING TOGETHER: GRASSROOTS CHILDCARE, URBAN INCLUSION, AND COLLECTIVE RESILIENCE - Saifudin Asrori; Muhammad Ismai’il; Ahmad Shabbir; Joharotul Jamilah (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. As urbanization accelerates in Indonesia, access to affordable, inclusive, and culturally relevant childcare remains a persistent challenge for urban families, particularly among working-class and marginalized communities. This study investigates Rumah Anak, a community-led childcare initiative in an urban neighborhood of Indonesia, to understand how grassroots caregiving models foster social cohesion, reciprocal care, and resilience amidst institutional fragmentation and resource scarcity. Using a qualitative case study approach that includes semi-structured interviews, participant observation, and document analysis, the research identifies three interrelated dynamics: trust-building and social bonding, reciprocal caregiving as a local ethic, and grassroots navigation of institutional ambiguity. The findings illustrate that Rumah Anak functions not merely as a substitute for formal daycare, but as a form of relational social infrastructure that strengthens community ties, supports maternal employment, and enhances child development. The study concludes that community-based childcare systems, when adequately supported, hold transformative potential for inclusive urban development and call for policy frameworks that center care as a shared civic responsibility. Abstrak. Di tengah percepatan urbanisasi di Indonesia, akses terhadap layanan pengasuhan anak yang terjangkau, inklusif, dan sesuai dengan konteks budaya masih menjadi tantangan besar, terutama bagi keluarga kelas pekerja dan kelompok marjinal. Penelitian ini mengkaji Rumah Anak, sebuah inisiatif pengasuhan anak berbasis komunitas di kawasan urban Indonesia, untuk memahami bagaimana model pengasuhan akar rumput mampu membangun kohesi sosial, praktik perawatan timbal balik, dan ketahanan kolektif di tengah fragmentasi kelembagaan dan keterbatasan sumber daya. Dengan menggunakan pendekatan studi kasus kualitatif melalui wawancara semi-terstruktur, observasi partisipan, dan analisis dokumen, penelitian ini mengidentifikasi tiga dinamika utama: pembangunan kepercayaan dan ikatan sosial, etika lokal dalam perawatan timbal balik, serta adaptasi komunitas terhadap ambiguitas institusional. Temuan menunjukkan bahwa Rumah Anak bukan sekadar alternatif dari daycare formal, melainkan berfungsi sebagai infrastruktur sosial relasional yang memperkuat jaringan komunitas, mendukung partisipasi kerja perempuan, dan meningkatkan perkembangan anak. Studi ini menyimpulkan bahwa sistem pengasuhan berbasis komunitas, jika didukung secara memadai, memiliki potensi transformatif dalam pembangunan kota yang inklusif dan menuntut kerangka kebijakan yang menempatkan perawatan sebagai tanggung jawab sipil bersama.